PENTINGNYA MEMAHAMI PERBUATAN HUKUM TELEKOMUNIKASI DALAM KERJASAMA ANTARA PT. IM2 DENGAN PT. INDOSAT - Harsono, Nonot (Jurnal Hukum dan Peradilan, 2015)
There is a difference between regulatory opinion of the Telecommunications Regulator/Ministry of Communications with the Corruption Court Judge on act did by PT. IM2 in collaboration with PT. Indosat. Title of cooperation between this service providers and network operators are "Internet access via cellular networks Indosat". In view of the regulator, this cooperation is in conformity with the regulations, even obligatory upon network operators to cooperate with the service provider. However, in view of the prosecutor and the judge, this cooperation violates the regulations. A difference of views between regulatory enforcement versus law enforcement is certainly very noteworthy because it will has very big impact to telecommunication development as the backbone of the national economy and the development of national legal systems and culture. Keywords: Networks, Network Usage, Frequency, Frequency Usage, Frequency Allocation, Frequency Allocation Usage